2020
DOI: 10.1186/s12864-020-6749-z
|View full text |Cite
|
Sign up to set email alerts
|

Host DNA contents in fecal metagenomics as a biomarker for intestinal diseases and effective treatment

Abstract: Background: Compromised intestinal barrier (CIB) has been associated with many enteropathies, including colorectal cancer (CRC) and inflammatory bowel disease (IBD). We hypothesized that CIB could lead to increased host-derived contents including epithelial cells into the gut, change its physio-metabolic properties, and globally alter microbial community and metabolic capacities. Results: Consistently, we found host DNA contents (HDCs), calculated as the percentage of metagenomic sequencing reads mapped to the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…Together, our results revealed correlated changes between marker species and metabolic pathways and suggested that both species and metabolic functions could be driven by the increased human-derived contents leaked into the gut due to CIB, consistent with our previous results ( 36 ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Together, our results revealed correlated changes between marker species and metabolic pathways and suggested that both species and metabolic functions could be driven by the increased human-derived contents leaked into the gut due to CIB, consistent with our previous results ( 36 ).…”
Section: Resultssupporting
confidence: 92%
“…Taxonomic analysis revealed that the alpha diversity was not significantly changed in all but one CRC data set (PRJDB4176) compared with their respective controls; conversely, alpha diversity was decreased significantly in patients of most CD data sets, while it did not show consistent trends in UC patients ( Table S1 , Wilcoxon rank sum test, P value <0.05). Interestingly, we found that the human DNA contents (HDCs), calculated as the percentage of sequencing reads mapped to the human genome, were significantly higher in patients in all diseases except one UC data set (PRJEB1220) ( Table S1 ), consistent with our results ( 36 ) showing that HDC could be used as a marker for intestinal diseases; the increased level of HDCs are likely due to the high level of deciduous epithelial and/or blood cells found in stools of patients with IBD or CRC, resulting from gut injury and quickening cell cycles ( 22 , 25 , 30 , 37 ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Artificial intelligence has recently attracted much attention in various fields of health and medicine. Different artificial intelligence and machine learning (ML) methods have been applied for various purposes, including image recognition, patient phenotyping, and outcome prediction for diseases such as cancer [15][16][17][18][19], cardiac arrest [20], Alzheimer's disease [21][22][23], respiratory diseases [24,25], rheumatic diseases [26], cornea and retinal diseases [27,28], gastrointestinal diseases [29,30], and infectious diseases [31][32][33][34][35]. These studies revealed that artificial intelligence has the capacity to assist clinicians in the disease diagnosis with high efficiency and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…So far, researches on the microbial ecology along the DT in ruminants mostly focus on rumen [27][28][29][30][31][32][33][34][35] with a few studies on gut/feces 36 , while other sites have been largely overlooked, despite accumulating evidence support their important roles. For example, in human, gut microbiota have been linked to many aspects of human life, including health 37,38 and diseases [39][40][41][42][43] , development 44,45 , responses to drugs and treatments [46][47][48] .…”
mentioning
confidence: 99%